2013
DOI: 10.5751/es-06045-180435
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Social Aspects of Ecological Restoration: New Challenges and Opportunities for Northern Regions

Abstract: ABSTRACT. Interest in ecological restoration has recently intensified as scientists, policymakers, and stakeholders use restoration in management strategies to address and mitigate global climate change and biodiversity loss. Northern ecosystems offer special challenges to restoration managers because of their short growing seasons and long recovery periods. This special feature of Ecology and Society on ecological restoration in northern regions draws together 11 papers based on presentations from the confere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…It depends. We would say that the best solution is focusing on the landscapes with intermediate resilience and low costs; however, the process of setting targets for restoration depends on human values, local demands, political situations, bureaucracy, and institutional arrangements (Rodrigues et al 2009, Faleiro and Loyola 2013, Nilsson and Aradóttir 2013, which make it a context-dependent process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It depends. We would say that the best solution is focusing on the landscapes with intermediate resilience and low costs; however, the process of setting targets for restoration depends on human values, local demands, political situations, bureaucracy, and institutional arrangements (Rodrigues et al 2009, Faleiro and Loyola 2013, Nilsson and Aradóttir 2013, which make it a context-dependent process.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent global meta-analysis on the ecological drivers of forest restoration success, Crouzeilles et al (2015) concluded that landscape restoration success is context dependent, but in general, it is influenced by the level of landscape connectivity and historic disturbance. Although there have been significant advances in increasing ecological resilience at a large scale, landscape restoration projects rarely incorporate socioeconomic dimensions despite aspects such as governance, social-political, and financial constraints being key determinants of restoration success (Aronson et al 1993, Rodrigues et al 2009, Nilsson and Aradóttir 2013. Thus, there is an urgent need to include the socioeconomic dimension in large-scale restoration initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal wetlands are easily blamed by the public as providing breeding ground for mosquitoes that can transmit life-threatening diseases (WHO, 2000;Dale and Knight, 2006). Social attitudes affect the implementation of coastal management and policies (Nilsson and Aradóttir, 2013). For example, worry about health risk brought by mosquitoes constrained the initiative of salt marsh restoration projects, since salt marsh restoration would introduce mosquitos (Adam, 2009).…”
Section: The Success Indicators Of Coastal Wetland Restorationmentioning
confidence: 98%
“…This low level of success can be attributed to the limited understanding of wetland functions, as well as some important scientific issues (i.e., the indicator system and the diagnosis of wetland degradation, the dynamic modeling and prediction of wetland degradation, the categories of wetland degradation, the success criteria and models, and the effectiveness of wetland restoration methods) (Xiao et al, 2002;Lv and Liu, 2008). Other factors include poor understanding of their self-designing capacities, the poorly defined success criteria of wetland restoration and the lagged monitoring of restoration projects (Nilsson and Aradóttir, 2013). Moreover, different coastal ecosystems receive disproportional attention.…”
Section: Issues Of Coastal Wetland Restoration and Success Evaluationmentioning
confidence: 99%
See 1 more Smart Citation